Penerapan Terapi Inhalasi Uap Minyak Kayu Putih dalam Mengatasi Bersihan Jalan Nafas Tidak Efektif pada Anak dengan ISPA - Aura Nur Hermanda Praja; Citra Setyo Dwi Andini (CV. ALIM'SPUBLISHING, 2026)
Acute Respiratory Infection (ARI) is one of the most common diseases in children and can cause ineffective airway clearance due to increased mucus production and secretion accumulation in the respiratory tract. This condition may result in symptoms such as productive cough, runny nose, fever, adventitious breath sounds, and increased respiratory rate, which can affect the child's comfort and daily activities. One of the non-pharmacological interventions that can be used to help manage this problem is eucalyptus oil steam inhalation therapy. This scientific paper aimed to describe the application of eucalyptus oil steam inhalation therapy for ineffective airway clearance in a child with ARI. The study employed a descriptive case study design involving a child diagnosed with ARI. Data were collected through interviews, observation, physical examination, and medical record review. A 9 year old child with acute respiratory infection (ARI) experienced a productive cough, a respiratory rate of 32 breaths per minute, and rhonchi in both lung fields. After receiving eucalyptus oil steam inhalation therapy for 10–15 minutes twice daily for three days, the respiratory rate decreased to 26 breaths per minute, secretions became more easily expelled, and rhonchi decreased. In conclusion, eucalyptus oil steam inhalation therapy may help improve airway clearance in children with ARI and can be used as a complementary intervention in pediatric nursing care.